If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (16 + -2x)(12 + -2x) = 96 Multiply (16 + -2x) * (12 + -2x) (16(12 + -2x) + -2x * (12 + -2x)) = 96 ((12 * 16 + -2x * 16) + -2x * (12 + -2x)) = 96 ((192 + -32x) + -2x * (12 + -2x)) = 96 (192 + -32x + (12 * -2x + -2x * -2x)) = 96 (192 + -32x + (-24x + 4x2)) = 96 Combine like terms: -32x + -24x = -56x (192 + -56x + 4x2) = 96 Solving 192 + -56x + 4x2 = 96 Solving for variable 'x'. Reorder the terms: 192 + -96 + -56x + 4x2 = 96 + -96 Combine like terms: 192 + -96 = 96 96 + -56x + 4x2 = 96 + -96 Combine like terms: 96 + -96 = 0 96 + -56x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(24 + -14x + x2) = 0 Factor a trinomial. 4((2 + -1x)(12 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(12 + -1x)' equal to zero and attempt to solve: Simplifying 12 + -1x = 0 Solving 12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12Solution
x = {2, 12}
| h=-0.44t^2+2.2t+10 | | y=-.6*55+22 | | y=-0.6*45+22 | | g(x)=4x^3 | | y=-.06*35+22 | | a^2-2a=100 | | y=-0.6*25+22 | | 1-4/x=2 | | 3+6s-2=6s+3-2s | | 6/(11y-1)=3/(5y-1) | | 5x/9=(x-5)/45 | | (w-y/2)(2) | | 9x+1=5x+11 | | (X-0.1)+1= | | 2y(4-2)=2/2 | | 6v+24=-4(7+5v) | | 7x-2+2x+8=180 | | -6x+4(3x+6)=26+4x | | 24-4n=-5(4-8n) | | 7+2y=5 | | 9+5+2k=6k-7 | | -(2v+2)=-12-7v | | x-2x^2=4x-4 | | 6x-21=3x-12 | | -16(4a-9b+2c)= | | (14/3)x=-126/11 | | 4(n+4)=-2+7n | | 4.2x+4=25 | | 5(x)X(25)2x=5 | | (957/14)x=18 | | 2(3x+5)+2(8x-7)=180 | | 112x5/14 |